Assessment of cell proliferation in knitting scaffolds with respect to pore‐size heterogeneity, surface wettability, and surface roughness. Issue 38 (24th June 2015) - Jo, A Ra; Hong, Myoung Wha; Cho, Yong Sang; Song, Ki Myoung; Lee, Jun Hee; Sohn, Dongwoo; Kim, Young‐Yul; Cho, Young‐Sam
ABSTRACT In this study, various types of poly(ε‐caprolactone) (PCL) knitting scaffolds were fabricated and analyzed to assess the cell‐culturing characteristics of knitting scaffolds with respect to pore‐size heterogeneity, surface wettability, and surface roughness. First, control knitting scaffolds were fabricated using 150‐µm‐diameter PCL monofilaments. Using chloroform and NaOH, PCL knitting scaffolds with varying roughness, pore‐size heterogeneity, and surface wettability were fabricated. Cell‐culture assessments were performed on these six types of PCL knitting scaffolds. Saos‐2 cells were used for cell assessments and cultured for 14 days on each scaffold. Consequently, heterogeneous pore‐size distribution and high surface wettability were found to enhance cell proliferation in knitting scaffolds. In addition, for highly hydrophobic knitting scaffolds exhibiting water contact angles greater than 110 degrees, smaller surface roughness was found to enhance cell proliferation. According to this study, in the case of knitting scaffold, NaOH‐treated knitting scaffold, without any control for the pore‐size homogenization, could be a candidate as the optimal knitting scaffold. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42566.